Determination of Magnesium, Zinc, and Reduced Glutathione Levels in Serum of Asthmatic Patients - Naji, N. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Asthma  is a disease  characterized by hyper reactivity  of the trachea and   bronchi   to  reversible   either   spontaneously  or  as  a  result   of treatment.In this study serum magnesium,  Zinc, and reduced glutathione  levelswere  meas ured  in  order  to  determine   their  levels  in  the  asthmatic patients and comparing  these levels with healthy controls.Fifty-  four  asthmatic   patients  were  enrolled  in  the  study  and  had their pulmonary  function test, and the levels of Mg,Zn, and GSH.Serum   magnesium   and  serum   zinc  were  determined   by  using Atomic  Absorption  Spectrophotometer . While serum glutathione was determined  by spectrophotometric analysis.The asthmatic  patients were divided into four groups according  to the  interpretation of  the  pulmonary  function  test  : severe  expiratory flow limitation, moderate  expiratory  flow limitation  , slight expiratory flow limitation and normal lung values .In  this  study,  it  was  found  that  serum  magnesium  levels  in  severe cases  of  asthmatic  patients  were significantly lower  than  the healthy control  population  (0.92 Â± 0.17mmol  I L vs.l.O1  Â± 0.19 mmol/L; (p